First report that prior ECMO therapy does not preclude hematopoietic cell transplantation. (19th May 2018) - Broglie, Larisa; Phelan, Rachel; Talano, Julie-An
Abstract: Hematopoietic stem cell transplantation (HCT) offers a potential cure for patients with high-risk malignancies but carries a risk of death from transplant-related complications. Extracorporeal membrane oxygenation (ECMO) is often considered a contraindication to transplant with the assumption that lung injury puts the patient at risk for pulmonary complications post-HCT. Although patients who have required prolonged intubation show gradual improvement in pulmonary function over time, there is little data on pulmonary functional recovery after ECMO which makes assessment pre-HCT difficult. We present a case series of two patients with high-risk hematologic malignancies, who had previously received ECMO and then underwent reduced-intensity HCT. Although both patients had complications post-HCT, neither patient suffered significant pulmonary toxicity related to their prior ECMO exposure. We conclude that, although patients who have previously been treated with ECMO remain at high risk for complications after transplant, but they should not be excluded from consideration for reduced intensity transplantation.